The Effect of Organizational Commitment on Service Performance: An Empirical Study at Public Health Center in Sorong Regency - Reijeng Tabara; Rahmad Hidayat Dongka (SENTRALISASI, 2021)
This study aims to determine the effect of organizational commitment on service performance in health centers all around Sorong district. This study was using Partial Least Squares (PLS) with Structural Equation Modeling (SEM) techniques to analyze 146 employees. The results showed that there was a positive and significant influence between organizational commitment to service performance with a T-statistic value greater than T-table (T-statistic 39.288> T-table 1.976) at a significance level of 5% (0.05). The results of this study have indicated that the higher the organizational commitment of employees, the better the service performance at health centers in Sorong district, West Papua.Â